111k views
4 votes
To find f(-3) substituteall of x in the equation and evaluate

To find f(-3) substituteall of x in the equation and evaluate-example-1

1 Answer

5 votes

ANSWER:

When evaluating x in the function we have that the function is not defined

Explanation:

We have the following function:


f(x)=(3x^2-8x-3)/(x^2-9)_{}

replacing x = -3, therefore:


\begin{gathered} f(-3)=(3\cdot(-3^2)-8\cdot-3-3)/((-3)^2-9) \\ f(-3)=(3\cdot9+24-3)/(9-9)=(48)/(0)=\text{ not defined} \end{gathered}

User Prudhvi Indana
by
6.0k points